High efficient photo detector by using ZnO nanowire arrays on highly aligned electrospun PVDF-TrFE nanofiber film. (18th June 2019) - Kang, Dong Hee; Kim, Na Kyong; Kang, Hyun Wook
Abstract: Zinc oxide(ZnO) is a versatile semiconductor material and its use is expanding into photoelectric applications. Anisotropic growth characteristics of ZnO are advantageous for growing a nanowire structure. ZnO nanowire based sensors exhibit enhanced performance in terms of photodetection due to their large specific surface area. ZnO nanowires on a highly aligned electrospun poly(vinylidene fluoride-co-trifluoroethylene) (PVDF-TrFE) nanofiber-based film are fabricated high performance ultraviolet (UV) detector. The movement of photo-induced electrons from ZnO nanowires is more effective in aligned electrospun film substrate (Rsq, off /Rsq, on = 551.0) than random electrospun film substrate (Rsq, off /Rsq, on = 47.8) under continuous UV irradiation. The current difference is 3.98 times higher on ZnO nanowires on aligned electrospun film than it is on random electrospun film in UV light on-off cycles. As a result, we improve the performance of photo sensitivity of electrospun nanofiber-based ZnO nanowires through controlling the directionality and fabrication time of the electrospun film without additional processes.